2016
DOI: 10.1063/1.4950796
|View full text |Cite
|
Sign up to set email alerts
|

Progress on electrocaloric multilayer ceramic capacitor development

Abstract: A multilayer capacitor comprising 19 layers of 38 μm-thick 0.9Pb(Mg1/3Nb2/3)O3–0.1PbTiO3 has elsewhere been shown to display electrocaloric temperature changes of 2.2 K due to field changes of 24 V μm−1, near ∼100 °C. Here we demonstrate temperature changes of 1.2 K in an equivalent device with 2.6 times the thermal mass, i.e., 49 layers that could tolerate 10.3 V μm−1. Breakdown was compromised by the increased number of layers, and occurred at 10.5 V μm−1 near the edge of a near-surface inner electrode. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 22 publications
3
22
0
Order By: Relevance
“…The results for the doped PMN‐8 PT MLCs showed lower values of the EC effect, as already observed in bulk ceramics. While the highest temperature changes of 1.36 K at Δ E =7 V μm −1 are in good agreement with values reported in literature for MLCs based on 0.9 Pb(Mg 1/3 Nb 2/3 )O 3 −0.1 PbTiO 3 , Δ T EC only reaches 0.78 K and 1.11 K for the manganese‐ and sodium‐doped PMN‐8 PT samples, respectively. In a previous publication we showed that dielectric and hysteresis losses were significantly reduced by manganese and lithium doping.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The results for the doped PMN‐8 PT MLCs showed lower values of the EC effect, as already observed in bulk ceramics. While the highest temperature changes of 1.36 K at Δ E =7 V μm −1 are in good agreement with values reported in literature for MLCs based on 0.9 Pb(Mg 1/3 Nb 2/3 )O 3 −0.1 PbTiO 3 , Δ T EC only reaches 0.78 K and 1.11 K for the manganese‐ and sodium‐doped PMN‐8 PT samples, respectively. In a previous publication we showed that dielectric and hysteresis losses were significantly reduced by manganese and lithium doping.…”
Section: Resultssupporting
confidence: 91%
“…Here, we report on the EC effect of PMN‐8 PT bulk ceramics and compare the results to multilayer structures of similar compositions reported previously . We investigate the influence of targeted doping by manganese and sodium on the EC temperature change Δ T EC and the thickness dependence of the electrical breakdown strength E D in PMN‐8 PT MLCs.…”
Section: Introductionmentioning
confidence: 76%
“…Here we investigate how thermocouple measurements of EC temperature change are influenced by the active/total volume ratio, using MLCs of (1 − x)Pb(Mg 1/3 Nb 2/3 )O 3 -xPbTiO 3 (PMN-PT, x ~ 0.1), which is known to be a good EC material based on studies of thin films [11], bulk samples [21][22][23] and MLCs [17][18][19]. We find that rapidly driven EC effects are highly adiabatic if measured near MLC face centres that lie sufficiently far from the inactive EC material.…”
Section: © 2017 Iop Publishing Ltd Printed In the Ukmentioning
confidence: 99%
“…Taking into account that fact that only a certain energy density might be stored in a dielectric (equivalent to a limit in electrostatic pressure), the value E max of metal oxide dielectrics is given by an empirical relationship [5]: [11], and solid solutions of [12], possess values of T C ε as high as a few 10 −2 K −1 . Here, in the limit of E = E max , Eq.…”
Section: Electrocaloric Effectmentioning
confidence: 99%